2019
DOI: 10.1071/sh19016
|View full text |Cite
|
Sign up to set email alerts
|

Should we still use azithromycin for gonorrhoea treatment?

Abstract: This review presents the evidence for azithromycin in the treatment of gonorrhoea, both as monotherapy and as a component of dual therapy. Uncertainties are explored regarding the efficacy of a dual treatment strategy, combining ceftriaxone and azithromycin, in the context of resistance trends and extra-genital infections. The association between microbiological testing and clinical outcome for the individual patient, and the effect of azithromycin use on other sexually transmissible infections, are considered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…3 Azithromycin 2 g more effectively cures azithromycin-susceptible gonococcal infections, compared to azithromycin 1 g. 115,128,143145 However, azithromycin 2 g single oral dose also results in more gastrointestinal side effects, particularly if taken on empty stomach. 144,146,147 Most important, severe vomiting needs to be avoided before the azithromycin dose has been absorbed, i.e. in about one hour, which reduces the efficacy.…”
Section: Therapymentioning
confidence: 99%
“…3 Azithromycin 2 g more effectively cures azithromycin-susceptible gonococcal infections, compared to azithromycin 1 g. 115,128,143145 However, azithromycin 2 g single oral dose also results in more gastrointestinal side effects, particularly if taken on empty stomach. 144,146,147 Most important, severe vomiting needs to be avoided before the azithromycin dose has been absorbed, i.e. in about one hour, which reduces the efficacy.…”
Section: Therapymentioning
confidence: 99%
“…It is suggested that the oropharynx plays an important role in gonorrhoea transmission due to previously unrecognised practices such as kissing 6 9 . Furthermore, the oropharynx is also responsible for the emerging antimicrobial-resistant N. gonorrhoeae due to the poor antibiotic penetration into the oropharyngeal mucosa 10 , 11 .…”
Section: Introductionmentioning
confidence: 99%
“…For this review, we will focus on gonorrhoea treatment because treatment failures are higher at the oropharyngeal site compared to genital infections [115,116 ▪ ] and treatment options are becoming scarce as N. gonorrhoeae has developed resistance to all classes of antibiotics [86,117]. There is no global consensus on a single recommendation for oropharyngeal gonorrhoea treatment (Table 5) [118]. The Australian and European guidelines recommend dual therapy with single doses of ceftriaxone (500 mg to 1 g) and azithromycin 2 g [97,119], while the US and UK guidelines recommend ceftriaxone monotherapy (500 mg to 1 g single dose) as the first-line treatment (Table 5) [79,120,121].…”
Section: Treatment For Oropharyngeal Infectionsmentioning
confidence: 99%